Imunitas Protektif Mencit Terhadap Cairan Kista Taenia saginata (PROTECTIVE IMMUNITY OF MICE AGAINST CYST FLUID OF TAENIA SAGINATA) - Dharmawan, Nyoman Sadra; Dwinata, I Made; Damriyasa, I Made; Oka, Ida Bagus Made; Swastika, Kadek; Anggreni, Luh Dewi; Astawa, Nyoman Mantik (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
The aim of this research was to determine immune response of mice against vaccines derived fromcyst fluid of Taenia saginata. The study was conducted using four BALB/c mice aged 6 weeks as experimentalanimals. All experimental animals were vaccinated intra peritoneal with Taenia saginata cyst fluidemulsified in Freund’s adjuvant. Immune response in the mice was determined by detecting antibodiesusing ELISA and by the presence of lymphocytes through evaluation of blood smear. The results showedthat the cyst fluid of Taenia saginata was antigenic and capable of inducing antibody responses that weredetected by ELISA. Mean antibody titers obtained in the results of the first, second, third, and fourth ofvaccination was 3.3 units; 17.9 units; 21.2 units; and 72.1 units; respectively. Evaluation of blood smear ofvaccinated mice showed an increase in the percentage of lymphocytes after vaccination with an average66.75%, compared with the average of lymphocytes before vaccination which was 40.75%. Further researchis still required in experimental animals by vaccination followed by challenge test with Taenia saginataeggs.
Keywords: immunity, protective, Taenia saginata cyst fluid